Integration of combined disease resistance for bacterial wilt and tolcv in tomato (Solanum lycopersicum L) through marker assisted selection - Belge Shriram Ashru (Centre for plant biotechnology and molecular biology, College of Horticulture, 2014)
Tomato (Solanum lycopersicum L.) is one of the most consumed vegetables after potato in the world and is an excellent plant genetic analysis system. It is grown in 0.88 million hectares area with 20.7 metric tonnes productivity in India (www.nbh.gov.in). The area under tomato cultivation in Kerala is very meagre. The main limiting factor is the incidence of bacterial wilt caused by Ralstonia solanacearum and ToLCV infection. The warm humid tropical climate and acidic soil conditions favor the incidence of this disease in Kerala. Crop loss upto 100 per cent is reported due to bacterial wilt. ToLCV affected plants exhibit curling, puckering, reduction in leaflet size, severe stunting and reduction in fruit set. However, severely infected plants almost fail to produce fruits. Traditional breeding at KAU has resulted in development of bacterial wilt resistant varieties (Sakthi, Mukthi and Anagha) which are susceptible to ToLCV. Genotypes resistant to different strains of ToLCV have been developed at Indian Institute of Horticulture Research. Genotypes with combined resistance and better agronomic traits are greatly warranted to improve tomato cultivation in problem areas. Molecular markers have been used extensively for genome mapping as well as identification and characterization of genes and QTL for many agriculturally important traits in tomato; including disease resistance. When sources of resistance to bacterial wilt (Sakthi) and tomato leaf curl virus (IIHR 2196) are available, these two characters can be combined in a single genotype with the help of marker assisted selection. Keeping this as the crucial aim, the present investigation was undertaken during 2013-2014 for screening of F3 population of a cross between Sakthi (BW resistant; low yield) and IIHR 2196 (ToLCV resistance; high yield) so as to integrate combined disease resistance along with better horticultural traits. Four mother plants selected from F2 population used for the study included F2-06, F2-18, F2-20 and F2-33 having both bacterial wilt and ToLCV resistance. Sixty seeds from each mother plant were used for raising F3 population. Two hundred F3 plants were evaluated for bacterial wilt and ToLCV disease reaction and important biometric parameters were recorded. Molecular markers reported earlier for bacterial wilt and ToLCV were validated on parents and F3 population. DNA isolated from parents Sakthi and IIHR 2196 were used to validate 14 ISSR, 14 SSR and 8 SCAR primers already reported for BW and ToLCV resistance. One ISSR, 3 SSR and 2 SCAR primers which showed polymorphism and reproducibility among parents were selected for F3 population screening. Biometric characters of F3 population raised in disease sick field were recorded along with disease reaction for bacterial wilt and ToLCV. Analysis of variance indicated superiority for F2-33 (1347.27 g) with respect to yield per plant. In F3 population 12 plants showed combined resistance for bacterial wilt and ToLCV and four of them were good yielders too (2575 to 3281 g/plant). Among the six selected primers used to screen the segregating population, only two each were found specific for bacterial wilt and ToLCV. The SSR LEaat 16 and TSCARAAG/CAT were identified for bacterial wilt and ISSR HB 12 and SCAR Ualty 16 for ToLCV. Since HB 12 is an ISSR marker, it has to be further validated before use in marker assisted selection. The other three primers selected can be recommended for marker assisted selection in tomato.